2007
DOI: 10.1007/s00213-007-0947-0
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2 receptor occupancy levels of acute sulpiride challenges that produce working memory and learning impairments in healthy volunteers

Abstract: Doses of sulpiride typically used in human cognitive studies produced low levels of DA D2 receptor occupancy compared to that considered efficacious in the treatment of schizophrenia. The levels of occupancy were sufficient to replicate impairments on a spatial working memory task and impair spatial learning. The relationship between occupancy and working memory was suggestive of presynaptic effects, although the precise mechanism underlying the impairment will require studies of wider ranges of occupancy with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 46 publications
7
41
1
Order By: Relevance
“…However, it is likely that too small a dose of sulpiride was used, resulting in the absence of any observable effect on brain activity. Although previous studies that used a 400 mg dose found subtle effects of neurocognitive testing (Mehta et al, 1999), a recent PET study by Mehta et al (2007) found that a single 400 mg dose of sulpiride (the same dose as used in the present study because of ethical constraints in testing higher doses) leads to only 28% occupancy of dopamine D 2 receptors in the striatum. In contrast, 60 mg of methylphenidate (the same dose as used in the present study) has been shown to lead to a much higher percentage occupancy (74%) of the dopamine transporter (Volkow et al, 1998).…”
Section: Discussionmentioning
confidence: 56%
“…However, it is likely that too small a dose of sulpiride was used, resulting in the absence of any observable effect on brain activity. Although previous studies that used a 400 mg dose found subtle effects of neurocognitive testing (Mehta et al, 1999), a recent PET study by Mehta et al (2007) found that a single 400 mg dose of sulpiride (the same dose as used in the present study because of ethical constraints in testing higher doses) leads to only 28% occupancy of dopamine D 2 receptors in the striatum. In contrast, 60 mg of methylphenidate (the same dose as used in the present study) has been shown to lead to a much higher percentage occupancy (74%) of the dopamine transporter (Volkow et al, 1998).…”
Section: Discussionmentioning
confidence: 56%
“…Second, previous reports have suggested association between psychosis and relatively greater D2 density in striatum, even though change is moderate (2). Third, clinical symptoms and cognitive deficits have been associated with abnormal D2 signaling (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The relationship between D2 receptors and cognitive deficits in schizophrenia is also supported by previous models postulating that relatively excessive D2 signaling may lead to lower cortical signal-to-noise ratio and reduced filtering of information, as well as blocking of distracting inputs (10)(11)(12).…”
mentioning
confidence: 83%
“…Striatal D 2 R activity is important for effective working memory as shown in animals and humans (e.g., Kellendonk et al 2006;Mehta et al 2008). Inactivation of striatal A 2A Rs might potentiate striatal dopaminergic signaling via D 2 Rs to produce the working memory enhancement, given the well-documented antagonistic A 2A R-D 2 R interaction in striatopallidal MSNs of the "indirect" pathway (Ferre et al 1997;Fredholm et al 2007).…”
Section: Selective Inactivation Of Striatal Neuronal a 2a Rs Is Suffimentioning
confidence: 99%